PENGARUH KONDISI EKONOMI MAKRO DAN PROSES MANAJEMEN RISIKO KREDIT TERHADAP NON-PERFORMING LOAN (Studi Kasus pada Bank X) - Hakim, Arif Rahman (Profit: Jurnal Adminsitrasi Bisnis, 2017)
Commercial banks is one of the vital industries within a modern economic system. The industry bridges the demands and supplies of money as the most important factor of production in the system. In line with its crucial role, bank’s failure may impose a financial crisis within the system when it take place in a systemic way. One of the most common causes for this failure is the high rate of non-performing loan (NPL), a condition where the debtors fail to pay money they borrow from a bank. In spite of the fact that this fail is caused by the dissatisfactory performance of the borrower, external factor such as macroeconomic condition and the internal banking system factor such as credit risk management appear to be the common factors to the crisis. This research tries to reveal the influence of macroeconomic condition and the process of credit risk management on the level of bank’s non performing loan by using a statistics modelling test. While the most of studies in the macroeconomics fields focuse the analysis on the secondary time series data, the current research employs primary data from questionnaire to take a closer look the perception of bank’s credit analists on the macroeconomic, credit management and NPL issues. The result taken from a case study in Bank X shows that there is a significat impact of macroeconomic condition, whether directly and indirectly through variable credit risk management process, on the degree of  bank’s non-performing loan.